A Rare Complication of Keratoplasty: Double Anterior Chamber - Köhle, Ülkü; Kan, Emrah; Yılmaz, Turgut (Fırat University, 2003)
Aim: We report a case in which, although we planned to perform a penetrating keratoplasty for corneal opacity, the host's Descemet's membrane became inadvertently detached and the operation resulted with double anterior chamber.

Amaç: Bu çalışmada, kornea opasitesi nedeni ile penetran keratoplasti uyguladığımız, ancak cerrahi sırasında hastanın kendi Desme'sinin dekole olması ile çift ön kamara oluşan bir olgu sunulmuştur.
Nadir Bir Keratoplasti Komplikasyonu : Çift Ön Kamara